A biometric-based secure, energy efficient, lightweight authentication protocol for wireless body area networks. (25th November 2021) - Vandana, T. Santhi; Venkateswarlu, S.
Wireless body area networks are one of the important categories of wireless networks for remote healthcare monitoring using wearable computing devices. In WBANs, it must be guaranteed that the privacy of users is not exposed to unauthorised entities while sending and receiving the data. Hence, a proficient and secure authentication protocol is highly essential in WBANs. Conventional security protocols have restricted and few protocols cannot protect the privacy of users. In this work, a secure, energy-efficient, lightweight authentication protocol is proposed for securing WBAN that performs authentication session key establishment in privacy-preserving data aggregation. The proposed protocol provides confidentiality, integrity, availability and authenticity of data. Based on the security analysis, it is clear that the proposed protocol provides powerful protection than majority of the available schemes in insecure channels.